On the relationship between public and private investment in the euro area - Christian Dreger; Hans-Eggert Reimers (European University Viadrina, Department of Business Administration and Economics, 2014)
This paper explores the long run relationship between public and private investment in the euro area in terms of capital stocks and gross investment flows. Panel techniques accounting for international spillovers are employed. While private and public capital stocks are cointegrated, the evidence is quite fragile for public and private investment flows. They enter a long run relationship only after fundamental drivers of private investment, such as demand and financing costs are included. According to the impulse response analysis, private investment reacts to shocks in public investment both in terms of stock and flow variables. In contrast, public investment is rather exogenous. Therefore, the lack of public investment might have restricted private investment and GDP growth in the euro area. The results have strong implications for the future direction of fiscal austerity programs to combat the euro area debt crisis.
Keywords: C23; E22; E62; 330; public and private investment; fiscal austerity; panel VAR